UNECE Countries in Figures 2017 - United Nations (United Nations, 2017)
UNECE Countries in Figures presents a profile of social and economic indicators for each of the 56 UNECE member countries. These profiles, prepared by the UNECE Statistical Division, are intended to be of interest to readers not necessarily familiar with statistical terminology or with interpreting statistical tables. This publication includes data collected from national and international sources of official statistics. The data are for the most recent year available.